Foreign Aid, Growth and Poverty : A Policy Framework for Niger - Pinto Moreira, Emmanuel (2012)
This paper extends the dynamic macroeconomic framework developed by Agenor et al. [Agenor, P.-R., Bayraktar, N., & Aynaoui, K. E. (2006, July). Roads out of Poverty? Assessing the Links between Aid, Public Capital, Growth, and Poverty Reduction. World Bank, Revised.]. As in the original model, linkages between foreign aid, public investment (education, infrastructure, and health) and growth are explicitly captured, but this time in a fixed nominal exchange rate regime. Although the nominal exchange rate is fixed, the relative price of domestic goods is endogenous, thereby allowing for potential Dutch disease effects associated with increases in aid. The impact of policy shocks on poverty is assessed by using partial growth elasticities. A policy experiment of increasing foreign aid illustrates the dynamic trade-offs between growth and poverty reduction in Niger.